Strengthening by intermetallic nanoprecipitation in Fe–Cr–Al–Ti alloy. (1st April 2016) - Capdevila, C.; Aranda, M.M.; Rementeria, R.; Chao, J.; Urones-Garrote, E.; Aldazabal, J.; Miller, M.K.
Abstract: The strengthening mechanism observed during ageing at temperatures of 435 and 475 °C in the oxide dispersion strengthened (ODS) Fe–Cr–Al–Ti system has been investigated. Atom probe tomography (APT) and high-resolution transmission electron microscopy (HRTEM) analyses determined that the alloy undergoes simultaneous precipitation of Cr-rich (α′ phase) and nanoscale precipitation of TiAl-rich intermetallic particles (β′ phase). APT indicated that the composition of the intermetallic β′ phase is Fe2 AlTi0.6 Cr0.4, and the evolving composition of α′ phase with ageing time was also determined. The results obtained from HRTEM analyses allow us to confirm that the β′ precipitates exhibit a cubic structure and hence their crystallography is related to the Heusler-type Fe2 AlTi (L21 ) structure. The strengthening could be explained on the basis of two hardening effects that occur simultaneously: the first is due to the α-α′ phase separation through the modulus effect, and the second mechanism is due to the interaction of nanoscale β′ particles with dislocations. Graphical abstract: